MAHARATA AL-ISTIQBAL FI AL-KITAB AL-MADRASI BI AL-MADRASAH AL-TSANAWIYAH AL-ISLAMIYAH - Muhammad Qadhafi (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This study aimed to identify the contents of listening and reading skills in the Arabic textbook “Durus al-Lughah al-Arabiyah.” This study was conducted qualitatively and employed a descriptive analysis technique. The population was the Arabic textbook which applied 2013 Curriculum for the tenth graders at the Islamic senior high schools. Data collection procedures involved making the checklist, analyzing the contents of the textbook, coding, tabulating data, and concluding. The research found both listening and reading skill materials in the textbook was sufficient according to Abd al-Rahman al-Fauzan. However, there were still some weaknesses. There were no introductory materials about the sound and the introduction of the long and short vowels. In addition, the CD/recording was unavailable for listening. Lastly, there was no picture in each title to help students’ comprehension. But, the content of listening and reading skills in the textbook were relevant to 2013 Curriculum for Arabic language subject.